Determinants of Inflation: Evidence from Nepalese Data - Neupane, Deepak (Janapriya Journal of Interdisciplinary Studies, 2022)
This study focuses on the examination of the relationship between the inflation and its major determinants in Nepal namely, GDP at constant price, investment, broad money supply, remittance, exchange rate, interest rate and inflation of India considering their log form using the data from 1980 to 2020 A.D. Augmented Dickey Fuller (ADF) test was adopted to examine whether the variables are stationary or not. The data under the consideration were integrated of different orders I (0) and I (1) so autoregressive distributive lag (ARDL) and bounds test was employed to make the analysis of the data. Vector auto regression (VAR) lag selection criteria was employed for the selection of the optimum lag length. The short run results show that the broad money supply, exchange rate and inflation of India are the significant determinants. Moreover, the results of F-statistic bounds test shows that GDP at constant price, broad money supply, exchange rate and Indian inflation are the major determinants of inflation in the long-run. The negative and significant value of the error correction term (ECT) imply that, the deviation in the long run increment in the inflation is corrected in the succeeding year. In addition, the results of the cumulative sum (CUSUM) and cumulative sum of square (CUSUMSQ) indicate the stability in the coefficients.